Comparative T2 and T1ρ mapping of patellofemoral cartilage under in situ mechanical loading with prospective motion correction. Issue 2 (3rd February 2017) - Lange, Thomas; Knowles, Benjamin R.; Herbst, Michael; Izadpanah, Kaywan; Zaitsev, Maxim
Abstract : Purpose: To demonstrate improved T 2 and T 1ρ mapping of patellofemoral cartilage with in situ loading by means of prospective motion correction and to assess load‐induced changes in healthy subjects. Materials and Methods: Established T 2 and T 1ρ mapping sequences were augmented with prospective motion correction based on optical tracking. Protocols were optimized for robust imaging of the patellofemoral cartilage at a field strength of 3T. Subjects were positioned in the scanner with knee flexion and in situ loading of the patellofemoral joint was performed with a pneumatic loading device. In a pilot study on a cohort of 10 healthy subjects, load‐induced T 2 and T 1ρ changes were evaluated through measurements with axial loads of 0/20/40 kg. Results: With prospective motion correction and additional lipid saturation, motion artifacts in patellofemoral cartilage magnetic resonance imaging (MRI) with in situ loading could be notably decreased, as demonstrated for T 2 mapping. The acquired relaxation maps suggested a T 2 / T 1ρ decrease in superficial cartilage and a T 2 / T 1ρ increase in deep cartilage under loading. However, in the quantitative group evaluation of the lateral patellar facet, only T 1ρ in superficial cartilage was significantly changed by loading ( P ≤ 0.05), while no significant T 2 differences for the three loading conditions were observed ( P ≥ 0.3). Conclusion: Prospective motion correction enables T 2 and T 1ρ mapping of patellofemoral cartilage with in situ loading and a comparison of the two contrasts in terms of their response to mechanical loading. T 1ρ is a more sensitive marker for load‐induced patellar cartilage changes than T 2 . Level of Evidence: 3 Technical Efficacy : Stage 1 J. MAGN. RESON. IMAGING 2017;46:452–460